2017
DOI: 10.1038/npp.2017.161
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Stress System Modulation of Sex Differences in Decision Making

Abstract: Maladaptive decision making is associated with several neuropsychiatric disorders, including problem gambling and suicidal behavior. The prevalence of these disorders is higher in men vs women, suggesting gender-dependent regulation of their pathophysiology underpinnings. We assessed sex differences in decision making using the rat version of the Iowa gambling task. Female rats identified the most optimal choice from session 1, whereas male rats from session 5. Male, but not female rats, progressively improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
48
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 59 publications
13
48
2
Order By: Relevance
“…These results are consistent with another a study using another type of risky decision making 20 task in which the risk of larger reward was associated with a negative consequence of footshocks (Orsini et al, 2016). On the other hand, Georgiou et al (2018) used a rat version of the Iowa Gambling Task (IGT) which required subjects are four choices with probability of 90%, 80%, 60% or 50% to receive 1, 2, 3 or 4 pellets of reward respectively, where the punishment was a 'time out' in the form of not receiving a reward for 10, 20, 30 or 40 seconds respectively before the next trial began. Over the course of learning, female rats tended to show a bias towards the most advantageous choice faster than males, whereas once both groups reached asymptotic levels of performance, male rats chose the most advantageous choice more often than females.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with another a study using another type of risky decision making 20 task in which the risk of larger reward was associated with a negative consequence of footshocks (Orsini et al, 2016). On the other hand, Georgiou et al (2018) used a rat version of the Iowa Gambling Task (IGT) which required subjects are four choices with probability of 90%, 80%, 60% or 50% to receive 1, 2, 3 or 4 pellets of reward respectively, where the punishment was a 'time out' in the form of not receiving a reward for 10, 20, 30 or 40 seconds respectively before the next trial began. Over the course of learning, female rats tended to show a bias towards the most advantageous choice faster than males, whereas once both groups reached asymptotic levels of performance, male rats chose the most advantageous choice more often than females.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, there are data on sex differences in stress regulation of serotonergic and dopaminergic systems; however, these data do not focus on arousal, but rather domains, such as depressive-like behavior and decision making (e.g. [121][122][123][124]). Thus, unlike in the LC, how sex and stress interact to modulate these other systems to regulate arousal has not been thoroughly explored.…”
Section: Sex Differences In Other Arousal Systemsmentioning
confidence: 99%
“…The lower binding potential in women in the striatum, however, is interpreted as increased dopaminergic tone 56,57 . In male rats, but not in female rats, a DRD2 antagonist eticlopride was previously shown to increase risky choice behaviours 58 . The same study showed a negative association between impulsivity and striatal DRD2 expression in male rats.…”
Section: Discussionmentioning
confidence: 98%